1921–2021: 100 years of macroseismic studies at BCSF - Sira, Christophe; Cara, Michel; Schlupp, Antoine; Masson, Frédéric; Schaming, Marc; Mendel, Véronique (Comptes Rendus. Géoscience, 2021)
The French Central Seismological Bureau (BCSF) was set up in Strasbourg in July 1921 by a governmental decision. Since then, BCSF is in charge of the macroseismic survey for the French territories. One of its main tasks is to determine macroseismic intensity in the different localities after each felt earthquake. This paper shows how the way of collecting macroseismic information evolved with time through the analysis of questionnaires sent to various dissemination networks and by using different methods and macroseismic scales. In context of a renewal of interest in macroseismic data, we present their main uses, as well as some perspectives for the forthcoming years. The quality of macroseismic data, together with the improvement of the analytical methods and the accessibility to BCSF data, in particular those from our archives, remain at the heart of our concerns and objectives.